AB0356 Building a patient-centred cardiovascular risk reduction program for patients with inflammatory arthritis. (12th June 2018) - Navarro-Millan, I.Y.; Young, S.; Shurbaji, S.; McDavid, C.; Cornelius-Schecter, A.; Johnson, B.; Cherrington, A.; Fraenkel, L.; Curtis, J.; Safford, M.
Abstract : Background: Cardiovascular disease (CVD) is the most common cause of death among patients with inflammatory arthritis (IA) such as rheumatoid arthritis (RA), psoriatic arthritis (PsA) or ankylosing spondylitis (AS). Objectives: This study is the formative work to help design a patient-centred intervention for a CVD risk reduction program for patients with IA. Methods: We conducted a qualitative study guided by Bandura's Social Cognitive Theory, placing special focus on knowledge about the relationship between arthritis and CVD as well as barriers and facilitators to receiving healthcare related to CVD risk such as screening and management for hyperlipidemia. Participants had to have either RA, PsA or AS and were recruited from a single academic centre. Data were analysed thematically. Results: We conducted three focus groups with a total of 17 participants. Mean age of participants was 56 (SD ±7.7) years; 15 were women; 3 were on a statin; and 1 previously had a stroke. The majority of the participants were Five themes emerged: 1) Need for more information about IA and medications; 2) Lack of education about CVD risk and IA; 3) CVD risk reduction as an integrated lifestyle modification; 4) Uses for peer support around relevant CVD risk factor mitigation approaches; and 5) Improving doctor-patient communication about RA. The themes that emerged in our study showed that the majority of these IA patients were not aware of the relationship between CVD and IA, and were very interested in learning about IA, medication side effects, and prognosis of IA. These participants wanted to learn first about IA and, as a secondary goal, learn about their CVD risk in the context of their IA rather than as a new condition. Conclusions: Providing a clear understanding about systemic effects of IA and how to treat it will be needed before focusing on CVD risk reduction. By doing so, there will be better opportunity for the CVD risk reduction program to succeed. Disclosure of Interest: I. Navarro-Millan: None declared, S. Young: None declared, S. Shurbaji: None declared, C. McDavid: None declared, A. Cornelius-Schecter: None declared, B. Johnson: None declared, A. Cherrington Grant/research support from: Boehringer Ingleheim, Consultant for: Novo Nordisk, Astra Zeneca, L. Fraenkel: None declared, J. Curtis: None declared, M. Safford Grant/research support from: Amgen, Inc